Enterobacteriaceae (Order Enterobacterales), Pseudomonas aeruginosa and Acinetobacter spp Carbapenemase producers isolated from patients hospitalized in ICU during the COVID-19 pandemic, 2020. - García-Cedrón, David Carmelo (2024)
The present study aimed to determine the type of carbapenemase present in Enterobactales, Pseudomonas aeruginosa and Acinetobacter spp. isolated from patients hospitalized in the ICU of Hospital IV "Víctor Lazarte Echegaray", during the COVID-19 pan-demic. In this descriptive, observational and cross-sectional study, biological samples were collected from patients hospitalized in the ICU, processed in the Microbiology Diagnostic Laboratory of Hospital IV "Víctor Lazarte Echegaray". Antimicrobial identification and sensitivity were performed with the AutoScan-4 automated system, and the RESISIT-3 O.K.N K-SET cassettes were used to identify the type of carbapenemase. Of a total of 129 cultures, 58,9% were found to be resistant to at least one carbapenem (Meropenem or Imipenem), of which 59,2% were Enterobacterales, 26,3% were Pseudomonas aeruginosa and 14.5% were% Acinetobacter spp; when evaluating the presence of carbapenemases, it was found that 66 cultures (51,2%) presented carbapenemases; of which 28 are positive to KPC (42,4%), 25 to NDM (37,9%) and 13 to OXA-48 (19,7%). It is concluded that the presence of carbapenemasas in microbial cultures isolated from patient hospitalized I the intensive care unit exceeds the 30% reported in 2019 in South America.